Climate change adaptation governance in Nepal: a framework for sustainable generation of adaptation services - Karki, G.; Bhatta, B.; Devkota, N. R.; Kunwar, R. M. (Banko Janakari, 2021)
Poverty and high dependency of rural and mountainous households on the natural resources of Nepal have made the country more vulnerable to climate change. On the other hand, there is inadequacy of adaptation services provided to the vulnerable households and ecosystems. Responding to climate change necessitates amore consolidated effort and effective implementation interventions from both the government and non-government actors. To help achieve this very essence, this study has aimed to- (i) review the existing climate change adaptation (CCA) practices, processes and patterns of sustainable resource mobilization and benefit sharing, and (ii) develop a framework that ensures sustainability of resources and equitable sharing of services and benefits accrued from CCA. Consultations with the communities, key state and non-state stakeholders both at federal and provincial levels, reviews of national policies, strategies, periodic plans and programs and field visits were carried out to synthesize the information, document the knowledge, and highlight the gaps pertaining to CCA. Qualitative Content Analysis (QCA) was executed for analyzing qualitative information. Recently, the Government of Nepal has developed a priority framework on sustainable resource management and delivery of adaptation services. In line with the eight themes identified by the National Climate Change Policy (NCCP, 2019), the proposed framework has paid central attention on medium and long-term adaptation planning adhered with Ecosystem-based Adaptation (EbA) and Community-based Adaptation (CbA). Building resilience, reducing vulnerability, increasing capacities, enabling environment, and integrating CCA in development planning have been the focus of the framework. It is found that the delivery of adaptation services to the climate vulnerable groups and poor communities is well reached out through CbA and EbA approaches. It is therefore, crucial in strengthening community- and locally-based mechanisms (such as forest-user groups, farmers groups, agricultural and fisheries cooperatives, and community networks) for sustainable management and delivery of services to facilitate effective adaptation.